STRENGTHENING OF FOUNDATIONS AND FOUNDATIONS (Spectrum Journal of Innovation, Reforms and Development, 2023)
The article analyzes the fact that the choice of method for strengthening foundations and foundations, the organization and technology of strengthening work largely depend on technology. Construction practice has proven that the service life of buildings and structures with sufficient maintenance during operation increases significantly and in many cases serves to prevent dangerous breakdowns and accidents. Cases of violation of the integrity of soils under existing foundations are discussed, as well as processes for stopping deformations of buildings and structures that are rapidly increasing over time.